Opsi Pendanaan Biodiversity di Indonesia - Haryanto, Joko Tri (Perhimpunan Biologi Indonesia, 2016)
The contribution of biodiversity to economic development, social and ecological in Indonesia today and thefuture are already being felt very real. Unfortunately, as well as economic development approach to the greeneconomy that appears on the answers rampant deforestation and forest degradation, biodiversity atmospheretoday in Indonesia is under pressure and decrease impact on the species and environmental balance problemsand poverty. Besides the problem of public funding also be other problems. In this case, government role to bevery significant through the Transfer to the Regions. By using the methodology analysis desk study, it can berecommended that General Allocation Fund (DAU) is the main policy priority for funding biodiversity, throughthe addition of indicators of the Fiscal Needs (KbF). Other policy options are DAK mechanism throughimprovement criteria.Keywords: Biodiveristy, General Allocation Fund (DAU), Specific Allocation Fund (DAK), Forestry,Environment